Sedative Power of Poetry: Study of Julia Darling's “The Poetry Cure”: Poder sedativo de la poesía: estudio de ''The Poetry Cure'' de Julia Darling - SALLOOM, Aida (Utopía y Praxis Latinoamericana, 2021)
ABSTRACTExpressing feelings creatively helps most of the patients cope with the vicissitudes of life and can be a lifeline for patients. This study aims to analyze the healing aspects of poetry in Julia Darling's “The Poetry Cure”. A qualitative method has been utilized, and discourse analysis has been carried out. The result shows that poetry can be clinically use as a therapeutic medium. Poet portrayed one of the main distributions of therapeutic poetry, which is to encourage and inspire the readers' positive emotion. Analyzed poems emphasized hope and its accompanying emotions. Recommendation for future research is provided by the end of the study. RESUMENExpresar los sentimientos de forma creativa ayuda a la mayoría de los pacientes a afrontar las vicisitudes de la vida y puede ser un salvavidas para los pacientes. Este estudio tiene como objetivo analizar los aspectos curativos de la poesía en ''The Poetry Cure'' de Julia Darling. Se ha utilizado un método cualitativo y se ha realizado un análisis del discurso. El resultado muestra que la poesía puede ser utilizada clínicamente como un medio terapéutico. Poet retrató una de las principales distribuciones de la poesía terapéutica que es alentar e inspirar la emoción positiva de los lectores. Los poemas analizados enfatizaron la esperanza y las emociones que la acompañan.